ANALYSE DE LA RENTABILITE DU SECTEUR HOTELIER A KINDU DE 2018 A 2020: CAS DES HOTELS VALANCIA, KARIBU ET JAY - Pierre, UTCHINGA WELA; KASIMU , GOMES YAHAYA (IJRDO - Journal of Business Management, 2022)
In conducting this research on the profitability of the hotel sector in KINDU, the major concern is to answer the following question: Is it worth investing in the hotel sector in KINDU?  To achieve this, we used inductive, comparative and analytical methods.  This was supported by documentary techniques and semi-structured interview for data collection, on the one hand, and the technique of financial analysis for their processing, on the other hand.  At the end of our analyses, the ratios obtained showed a real position of financial independence of the hotel sector at KINDU.  Nevertheless, we have also observed that despite this financial independence of the sector, the economic, financial and commercial returns are positive, but low.  This situation is the logical consequence, not only of the low purchasing power of the population, but also of the isolation of the city following the transport difficulties that the city isang through on all possible means of communication.